The Psychology of Conflict: Mediating in a Diverse World, by Paul Randolph (Bloomsbury, 2016). Issue 2 (7th September 2017) - Stuart, Stephanie
Abstract : The Psychology of Conflict: Mediating in a Diverse World, by Paul Randolph (Bloomsbury, 2016)